An Approach To Address Sexual Misconduct Through The Lessons Found In The Stories Of Prophet Joseph And Prophet Luṭ In The Quran - Ahmad Murshidi Mustapha; Mohd Zahir Abdul Rahman; Mohd Miqdad Aswad Ahmad (HUMAN RESOURCE MANAGEMENT ACADEMIC RESEARCH SOCIETY, 2024)
Indexed by ERA